2012
DOI: 10.1016/j.buildenv.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-technical barriers to energy model sharing and reuse

Abstract: An energy model generated during the design phase of a building could -in principal -be converted into a calibrated energy model and used to improve the building's operational performance. However, this rarely happens in practice. Through a survey of 306 building professionals, this research investigates whether this model reuse is technically feasible, based on today's design-phase models, and what non-technical barriers might stand in the way of its implementation. An important finding is that 75% of the eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…However, according to the literature there are still limitations or barriers which restrict the use of BPS in the industry. A survey study by [15] found that the BPS industry in the United States (US) is premature and needs to develop more. Furthermore, a survey study in China identified the time it The main principles to design energy-efficient buildings include designing sustainable solutions, applying energy efficiency measures and incorporating renewable energy technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the literature there are still limitations or barriers which restrict the use of BPS in the industry. A survey study by [15] found that the BPS industry in the United States (US) is premature and needs to develop more. Furthermore, a survey study in China identified the time it The main principles to design energy-efficient buildings include designing sustainable solutions, applying energy efficiency measures and incorporating renewable energy technologies.…”
Section: Introductionmentioning
confidence: 99%
“…This practice diminishes the effectiveness of energy models, as there is a widely shared believe within the modeling community that the early use of simulation tools yields to more cost and energy effective design solutions (Samuelson et al 2011). However, even architects who are committed to 'building green' and who are thus commissioning energy simulations during schematic design, often face the impediment that they do not know how to read and act upon the outcomes of energy simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, as Samuelson, Lantz, and Reinhart (2012) surveyed, a very few number of design offices, even firms having in-house environmental design teams, make early decisions such as layout planning based on performancebased feedback because of the slow pace and complicated nature of thermal modelling.…”
Section: Thermal Zoning and Architectural Space Layout 121 Space Pmentioning
confidence: 99%